Understanding the Dynamics of Telework: A Job Demands–Resources Model-Based Qualitative Analysis of Employee and Managerial Experiences in Romania - Cristina Veith; Mihaela Minciu; Daniel Constantin Bojin (Journal of Theoretical and Applied Electronic Commerce Research, 2025)
Telework has become a crucial element of the modern business landscape, driven by transformations sparked by multiple global crises. The transition from traditional, in-office work to telework, sometimes mandated by revolutionary circumstances (such as the COVID-19 pandemic), has highlighted both the advantages and challenges associated with this mode of work organization. In this context, the present study examines the effects of telework as experienced by employees and managers during two key periods: the COVID-19 pandemic and the introduction of chatbots. Through 24 interviews conducted and analyzed across these two timeframes (2021 and 2024) using NVivo 14 Windows software, the data were organized and interpreted within the framework of the Job Demands–Resources (JD-R) model. The main findings focus on organizational communication, sustainability, and work efficiency, while also highlighting associated benefits and drawbacks. The results demonstrate the importance of adapting organizational resources to meet growing job demands in order to maintain desired levels of efficiency and effectiveness while avoiding burnout, productivity declines, or other negative outcomes in the context of telework. This research contributes to understanding the evolution of telework by offering practical insights for sustaining high levels of motivation and workforce engagement in achieving organizational objectives in the hybrid work era. This paper emphasizes the significance of the JD-R Model in analyzing dynamic work environments, providing relevant perspectives for organizations on the continuously evolving dimensions of job demands, job resources, and outcomes.